A HYBRID INTEROPERABILITY MODEL FOR VILLAGE INFORMATION SYSTEMS: ADAPTIVE DIGITAL GOVERNANCE IN RURAL AREAS OF GARUT REGENCY, INDONESIA - Zulkifli Adnan; Abdullah Ramdhani; Hasbi Shiddiq Fauzan; Jumiati (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2026)
Digital transformation has become an important component of public sector reform, including at the village level. However, the implementation of Village Information Systems in rural areas continues to face challenges associated with unstable internet connectivity, fragmented administrative applications, limited human capacity, and inconsistent data management. These conditions affect the effectiveness of Electronic-Based Government Systems (SPBE) and hinder the continuity of public services. This study aims to examine digital governance challenges in village administrations and develop a conceptual Hybrid Interoperability Model for Village Information Systems in Garut Regency, Indonesia. A qualitative descriptive approach was employed using semi-structured interviews, observations, and document analysis involving 19 informants from village governments, district institutions, Diskominfo, and DPMD. Data were analyzed using thematic analysis. The findings reveal that fragmented systems and infrastructure limitations represent not only technical issues but also institutional challenges that influence administrative performance. In response to these conditions, the study proposes a Hybrid Interoperability Model that emphasizes administrative continuity, institutional coordination, and adaptive digital governance. The study contributes to the literature by reconceptualizing interoperability as a governance mechanism rather than merely a technological function. Practically, the findings provide insights for SPBE implementation and village governance reform in rural contexts characterized by infrastructural uncertainty and unequal digital capacities.